Oxygen atom density in a large reactor powered by four inductively coupled plasma sources. (May 2022) - Primc, Gregor; Lojen, Dane; Vesel, Alenka; Mozetič, Miran; Zaplotnik, Rok
Abstract: Gradients in O-atom density in metallic plasma reactor useful for rapid surface activation of 3D polymer products have been measured. The reactor of a volume of 150 l was equipped with four inductively coupled plasma sources (ICPS) of (predominantly) oxygen atoms, parallelly coupled with a radio-frequency generator of adjustable power up to 5 kW at 13.56 MHz. Molecular oxygen was continuously introduced into the ICP sources, where it was dissociated upon plasma conditions. The constant pumping of the plasma reactor enabled the effective transfer of O-atoms from the ICP sources, so that their density remained high in the entire chamber even far from plasma sources. The O-atom density was measured across the reactor with a movable catalytic probe calibrated for oxygen. The sophisticated immersible design enabled the O-atom density to exceed 10 21 m −3 in the major chamber volume at the pressure of 20 Pa. At this pressure, a uniform plasma in the H-mode was sustained at the total real RF power of 1800 W. Significant gradients in the O-atom density were only detected next to ICP sources' exhausts and in the main chamber's metallic side tubes. Such uniform distribution of O-atoms in a large reactor is advantageous for rapid surface activation of 3D polymer products. Highlights: Four inductively coupled plasmas were integrated into a metallic vacuum chamber of volume 150 l Dense plasma was confined to the volume of high electromagnetic field Density of neutral oxygen atoms was measured with a movable probe Dissociation fraction over 10% was obtained throughout the metallic chamber